Langgar - Sein Ruffedge, (Syed Hussein Syed Mustafa); Hans Isaac; Adi Putra; Khir Rahman; Natasha Hudson; Namron (Kuala Lumpur : Tayangan Unggul Sdn. Bhd, 2013)
Langgar tells the story, of Nizam, who seeks justice for the with of his beloved wife, Aina and his child, whom she was pregnant with at the time as a result of rape and murder by a gang. It is Nizam's solemn promise to himself that everyone involved in the rape-murder must be wiped from the face of earth. Nizam is introduced to Radzi's gang by Khairul, an old friend. Radzi's gang is one of the more feared, dabbling in night clubs, drugs and illegal money lending. After he is tested by Loy, radzi's right-hand man, Nizam joins Radzi's gang as a debt collector. Among the names listed in the file are Aina and her father, under debtors who have failed to pay. Nizam is now convinced that he is on the right track.
Pengarah fotografi, Mohd Noor Mohd Kassim ; penerbit eksekutif, Gayatri Su-Lin Pillai, Hazil Izham Ismail ; penyunting, Nazim Shah.
Hans Isaac, Adi Putra, Khir Rahman, Natasha Hudson, Namron.
LPF: 18
DVD format, NTSC, Dolby Digital (5.1 AC3).
Title from title screen.
Keywords: Crime films; Gangster films; Thrillers (Motion pictures).; Love in motion pictures